Efektivitas Layanan Penguasaan Konten Menggunakan Model Pembelajaran Kooperatif Tipe Think Pair Share untuk Meningkatkan Keterampilan Bertanya Siswa dalam Belajar - Aldio Kyoto Putra; Firman Firman; Syahniar Syahniar (Universitas Negeri Padang, 2019)
Student with low asking skills tend to experience obstader in the learning process. Actually, the effort given by the counseling teacher hasn’t reached the taarget sa expected. This study aims to see the effectiveness of content mastery services using cooperative learning model type think pair share, to improve student questioning skills. This study uses a quantitative approch with design quasy experiment type the non equivalent control group in SHS N 1 Sungai Limau Kab. Padang Pariaman. The subjects are XI IPS 1 & 3 class. Data collection techniques used questionnaire, than analyzed by different test technique wilcoxon and t-test. Research result show content mastery services used cooperative learning model type think pair share can improved student questioning skill and more effectiv than content mastery service without used learning model. Counseling teachers are expected to improve student’s questioning skill throught countent mastery services used cooperative learning proccess type think pair share.